A device to detect leakage at the patient end of total intravenous anaesthesia. (17th February 2022) - Chandran, Rajkumar; De Sousa, Kalindi; Koo, Seok Hwee; Lim, Yin Yu; Shang, Lei; Paiputra, Fleming; Tan, Joanne Huishan; Ching, Terry Tsz Him; Khoo, Xiaojuan
Abstract: The use of total intravenous anaesthesia (TIVA) is limited by concerns of disconnections of the tubing, resulting in accidental awareness. We designed a sensor device to detect leakages at the patient end and notify the medical personnel, thereby allowing immediate intervention in preventing awareness. For moisture detection, resistive sensing was selected as the working principle. The prototype was in proximity to the tubing from the TIVA pump and the patient's intravenous cannula, and able to detect leakages in all potential leakage sites and activate an alarm. Our device consists of a disposable bandage (sensor), attached to a reusable clamp that is directly coupled to a central module (SparkFun MicroView, a small microcontroller with built-in Organic Light-Emitting Diode (OLED) display). The disposable bandage is wrapped around the possible leakage sites. Crucially, the disposable bandage is integrated with two separate moisture sensing threads. When moisture is present, the central module detects a drop in resistance across the moisture sensing threads and activates a flashing LED and buzzer. We have successfully created a functional leak detection device, comprising a moisture sensing bandage and an audio and visual alert system, to address the problem of undetected TIVA leakages at the patient end.